Continuities in late antique literacy: the evidence from North Africa and Gaul - Várhelyi, Zsuzsanna (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In this article I reconsider the evidence for ancient literacy from late antique North Africa and Gaul in order to reassess how the end of the “epigraphic habit” in the third century may have changed the popular contexts and notional associations of writing. Analyzing evidence for the Christian “epitaphic habit,” as well as for the production of legal and economic documents between the third and sixth centuries CE, I propose that late antique uses of writing attest to numerous continuities with their early imperial counterparts, including an interest not only in the pragmatic but also the performative character of ancient literacy.